2013
DOI: 10.1242/jcs.122952
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of chemoattractant receptors regulates chemotaxis, actin re-organization, and signal-relay

Abstract: SummaryMigratory cells, including mammalian leukocytes and Dictyostelium, use G-protein-coupled receptor (GPCR) signaling to regulate MAPK/ERK, PI3K, TORC2/AKT, adenylyl cyclase and actin polymerization, which collectively direct chemotaxis. Upon ligand binding, mammalian GPCRs are phosphorylated at cytoplasmic residues, uncoupling G-protein pathways, but activating other pathways. However, connections between GPCR phosphorylation and chemotaxis are unclear. In developing Dictyostelium, secreted cAMP serves as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 74 publications
0
40
0
Order By: Relevance
“…Attraction to chemokines in leukocytes has been shown to utilize both β-arrestins and receptor phosphorylating G protein receptor kinases (GRKs) to regulate migration [28,29]. Receptor phosphorylation is also important in regulating ligand affinity for the cAR1 receptor in Dictyostelium , although there are contradictory reports as to what effects this phosphorylation may have on downstream signal transduction and adaptation [30-32]. Although the intricate details of receptor and G protein function, including receptor-ligand interaction and the regulation of the heterotrimeric G protein cycle, are not addressed here, excellent reviews on these topics can be found in: [33-37].…”
Section: Chemotactic Network Of Dictyostelium and Leukocytesmentioning
confidence: 99%
“…Attraction to chemokines in leukocytes has been shown to utilize both β-arrestins and receptor phosphorylating G protein receptor kinases (GRKs) to regulate migration [28,29]. Receptor phosphorylation is also important in regulating ligand affinity for the cAR1 receptor in Dictyostelium , although there are contradictory reports as to what effects this phosphorylation may have on downstream signal transduction and adaptation [30-32]. Although the intricate details of receptor and G protein function, including receptor-ligand interaction and the regulation of the heterotrimeric G protein cycle, are not addressed here, excellent reviews on these topics can be found in: [33-37].…”
Section: Chemotactic Network Of Dictyostelium and Leukocytesmentioning
confidence: 99%
“…Hypersensitivity to cAMP could also explain the observed effect of HectPH1 disruption in the AX2 background, namely a delay of few hours in the beginning of aggregation and a lower efficiency of aggregation. In contrast to HSB1 HectPH1− , the AX2 HectPH1− strain would resemble AX2 cells exposed to high concentrations of cAMP, which is known to inhibit, rather than stimulate, cAMP-dependent developmentally-regulated gene expression as well as cAMP relay (Rossier et al, 1979;Mann and Firtel, 1987;Brzostowski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Upon cAMP binding, the cAR1 receptors are phosphorylated, with phosphorylation inducing loss of ligand binding (Kim et al, 1997). Inhibiting phosphorylation results in unaltered ligand binding, which leads to formation of smaller aggregates and disruption of cell streaming (Brzostowski et al, 2013), a phenotype resembling the HSB1 HectPH1− mutant. It is possible that HectPH1 ubiquitylates the cAR1 receptors or arrestins (Cao et al, 2014), with its disruption favouring membrane exposure of the receptors, thus increasing Northern blots of total RNA extracted at the indicated times from starving cells, treated or not with cAMP pulses, and labelled with csA, carA or, for normalization, hstA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests a revision of this view: using improved assays, cells with non-phosphorylatable cAR1 receptors can be seen to chemotax poorly and produce cyclic-AMP for prolonged periods, indicating that at least some adaptive processes emanate from receptor phosphorylation [32 ].…”
Section: Receptor-proximal Signalling and Adaptationmentioning
confidence: 99%